2017
DOI: 10.1063/1.4977057
|View full text |Cite
|
Sign up to set email alerts
|

Sparse identification of a predator-prey system from simulation data of a convection model

Abstract: The use of low-dimensional dynamical systems as reduced models for plasma dynamics is useful as solving an initial value problem requires much less computational resources than fluid simulations. We utilize a data-driven modeling approach to identify a reduced model from simulation data of a convection problem. A convection model with a pressure source centered at the inner boundary models the edge dynamics of a magnetically confined plasma. The convection problem undergoes a sequence of bifurcations as the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(56 citation statements)
references
References 29 publications
0
55
0
Order By: Relevance
“…For example, stable shear flows can dramatically quench turbulent transport by shear-induced-enhanced-dissipation (see, e.g., [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]). This occurs as a shear flow distorts fluid eddies, accelerates the formation of small scales, and dissipates them when a molecular diffusion becomes effective on small scales.…”
Section: Introductionmentioning
confidence: 99%
“…For example, stable shear flows can dramatically quench turbulent transport by shear-induced-enhanced-dissipation (see, e.g., [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]). This occurs as a shear flow distorts fluid eddies, accelerates the formation of small scales, and dissipates them when a molecular diffusion becomes effective on small scales.…”
Section: Introductionmentioning
confidence: 99%
“…In [17], the authors proposed an adaptive SINDy algorithm for discovering PDE, which iteratively applies ridge regression with hard thresholding. Additional approaches for model identification can be found in [5,8,10,11,14,16,22,24].…”
Section: A)mentioning
confidence: 99%
“…Loiseau et al [49] also demonstrated the ability of SINDy to identify dynamical systems models of high-dimensional systems, such as fluid flows, from a few physical sensor measurements. SINDy has also been applied to identify models in nonlinear optics [50] and plasma physics [51]. For actuated systems, SINDy has been generalized to include inputs and control [52], and these models are highly effective for model predictive control [53].…”
Section: Sindy: Sparse Identification Of Nonlinear Dynamicsmentioning
confidence: 99%